Effect of Salak Seed Flour (Salacca edulis) and Tapioca Flour Addition on the Quality of Chicken Meatballs - Ismuning Dinar Rahmani, Ismuning; Sarofa, Ulya; Winarti, Sri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The meatballs are a food that all people of various ages favor because they taste good and are nutritious. In this study, chicken meatballs will be made with salak seed flour and tapioca flour. The purpose of this study was to determine the effect of the addition of salak seed flour (Salacca edulis) and tapioca flour on the quality of chicken meatballs and to determine the best treatment for the addition of salak seed flour (Salacca edulis) and tapioca flour on the quality of chicken meatballs that consumers like. This study uses the method of Completely Randomized Design (CRD) factorial pattern consisting of 2 factors, where Factor l is the concentration of salak seed flour consisting of three levels (5%, 10%, and 15%) and Factor ll is the concentration of tapioca flour consisting of three levels (25%, 30%, and 35%). The data from the analysis were processed using Analysis of Variance (ANOVA) to determine the presence of significant differences in each treatment. If there is a significant difference, further tests are carried out with the DMRT (Duncan Multiple Range Test) method at 5%. Chicken meatballs obtained the best treatment results with the treatment of adding the concentration of salak seed flour and tapioca flour (10%: 35%) which produced a yield value of 107.75%, moisture content of 69.56%, fat content of 5.48%, protein content of 15.50%, WHC 18.68%, chewiness (hardness 234.93 N and cohesiveness 0.50 mJ), as well as color (4.20), aroma (4.17), taste (4.03) and texture (3.37). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and Infrastructure